2012
DOI: 10.3109/00498254.2012.723151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fibrosis in precision-cut tissue slices

Abstract: 1.In this review, the use of precision-cut tissue slices (PCTS) of the liver, kidney, lung and intestine in fibrosis research are evaluated and future possibilities are discussed. 2.In vivo models or techniques that are applicabless to be investigated in PCTS are discussed. 3.It is concluded that the early onset of fibrosis can be induced successfully in PCTS prepared from human and experimental animals. 4.Moreover, precision-cut slices of fibrotic tissue are effective in gaining new knowledge of the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 162 publications
2
41
0
Order By: Relevance
“…These effects were observed in PCLuS but not in PCKS. This could perhaps be caused by differences in the amount and type of immune cells present in both tissue types, as mentioned previously [6]. As these reductions are similar between non-targeting and Gapdh-targeting Accell siRNA, we hypothesize that Accell siRNA acts as an antagonist on siRNA sequence-independent proteins PKR and RIG-1, which are both present in the cytoplasm.…”
Section: Slice Inflammationmentioning
confidence: 86%
See 1 more Smart Citation
“…These effects were observed in PCLuS but not in PCKS. This could perhaps be caused by differences in the amount and type of immune cells present in both tissue types, as mentioned previously [6]. As these reductions are similar between non-targeting and Gapdh-targeting Accell siRNA, we hypothesize that Accell siRNA acts as an antagonist on siRNA sequence-independent proteins PKR and RIG-1, which are both present in the cytoplasm.…”
Section: Slice Inflammationmentioning
confidence: 86%
“…PCTS refer to viable explants, with a welldefined thickness and diameter, prepared from tissue (e.g., lung and kidney) that can be cultured ex vivo [5,6]. In comparison to conventional in vitro models, PCTS offer crucial advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have been performed with brotic liver slices derived from animal models of chemicallyinduced brosis. 94 These studies focused on antibrotic therapy, 105,106 the detection of biomarkers and the mechanism of brosis. 107,108 Veidal et al 107 showed that a specic fragment of type III collagen generated by metalloproteinase-2 and metalloproteinase-9 by brotic liver slices is a biomarker for liver brosis.…”
Section: Precision-cut Liver Slices In Liver Fibrosismentioning
confidence: 99%
“…PCTS represent an ex vivo tissue culture technique that replicates most of the multicellular characteristics of whole organs in vivo. 94 Recently, the utilisation of PCTS for the study of organ brosis has been reviewed. 94 Particularly, the possibility of using (diseased) human tissue to study mechanisms of brosis has the potential to become a great asset of the PCTS technique.…”
Section: Fibrosis In Liver and Intestinementioning
confidence: 99%
See 1 more Smart Citation